Ungovernability and ungovernable life in Palestine. (October 2022) - Joronen, Mikko; Griffiths, Mark
Abstract: This paper elaborates the notion of ungovernability as an irresolvable condition of living. It begins by identifying three distinct modes of ungovernability in current geographical work on Palestine: ungovernability as a failure to govern ; as a rationale for governing ; and as a technique of governing . To this we develop a further conceptualisation of ungovernability as a condition of living that, firstly, remains irreducible to the strategic domain of governing. Secondly, we argue, by drawing on prevalent geographical work on vulnerability and woundedness, that ungovernability constitutes an irresolvable origin of governing that, on the one hand, makes governing incapable of sustaining what it claims for itself, while on the other, names the starting point of a critical analysis of power. By placing the irresolvable ungovernability at the centre of analysis we offer, through examples drawn from our fieldwork in Palestine, an approach that does not reduce life at the outset to cycles of domination-resistance but instead approaches life and its spaces through those ways they remain irreducible to, and thus ungovernable for various forms of governing.